Students’s Use Of Technology - Selmani, Alma; Musabelliu, Gerta (European Scientific Journal, ESJ, 2016)
Technological developments that occurred in the late twentieth century and early twenty-first century, increased the use of technology in almost every aspect of human life and also its importance. The evolution of technology has meant that today anyone can use it at any time: everyone can have access to the Internet for different purposes. This thesis will focus on learning technology in higher education in Albania and specifically will use a survey on the use of technology by students of the Faculty of Economy during their studies. The main purpose of this work is to examine how much support there is and how students use technology in their learning process. The task has three main objectives: • To determine the attitudes and the degree of acceptance of technological change from students of faculty • To determine the extent of use of technologies during their studies, analyzing the types of technology frequently used by. • To determine how e-learning is recognized and how necessary is its usage by students’s perspective. The methodology used is a qualitative analysis conducted through the distribution of questionnaires to students of faculty, as the main stakeholders of this research. Finally, from the analysis conducted it is concluded that students prefer technology; the most used technology is the laptop, less used is Instant Messaging and recognition of the concept of e-learning is at the average level, but still seen as a possibility to have a better study.